2016
DOI: 10.1007/s10554-016-1026-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left atrial appendage function and thrombi in patients with atrial fibrillation: from transthoracic to real time 3D transesophageal echocardiography

Abstract: The detection of embolic sources in patients with atrial fibrillation (AF) is important to guide anticoagulant therapy. Two-dimensional transesophageal echocardiography (TEE) is the gold standard to study left atrial appendage (LAA) anatomy and morphology, despite some false-positive diagnosis. We hypothesized that real time 3D TEE (RT3DTEE) is superior to 2DTEE in detecting and/or excluding LAA thrombi. We studied 93 patients with non-valvular AF (60 males, age = 67.1 ± 14.2 years) referred for electric cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In fact, though transthoracic (TTE) and transoesophageal echocardiography (TEE) are available in the clinic to measure the blood flow velocity in both the LA and the LAA, both techniques can only provide average information on the velocity magnitude and direction in the sampling volume, without being able to give detailed spatial 3D information on the local flow conditions (30, 31). Ideally, 4D flow MR could provide similar information as the CFD analysis, but the spatial resolution, typically larger than 1 mm voxel, is not sufficient to assess a small region such as the LAA, and is thus not yet suitable for clinical applications (32).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, though transthoracic (TTE) and transoesophageal echocardiography (TEE) are available in the clinic to measure the blood flow velocity in both the LA and the LAA, both techniques can only provide average information on the velocity magnitude and direction in the sampling volume, without being able to give detailed spatial 3D information on the local flow conditions (30, 31). Ideally, 4D flow MR could provide similar information as the CFD analysis, but the spatial resolution, typically larger than 1 mm voxel, is not sufficient to assess a small region such as the LAA, and is thus not yet suitable for clinical applications (32).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the effect of IVT morphology on the surgical outcome, however no study to our knowledge has ever included hemodynamic analysis of IVT morphology to investigate the effect of IVT morphology on the P. The main reason why we adopted the CFD analysis was that computational modeling enabled a quantitative analysis of fluiddynamic parameters, such as velocity streamlines and pressure, which were impossible to measure non-invasively in clinics with sufficient accuracy. In fact, although transthoracic (TTE) and transoesophageal echocardiography (TEE) are available in the clinic to measure the blood flow velocity in IVT, both techniques can only provide average information on the velocity magnitude and direction in the sampling volume, without being able to give detailed spatial 3D information on the local flow conditions (Fukuda et al, 2003;Dentamaro et al, 2017). Therefore, it is impossible to accurately evaluate the hemodynamics of IVT morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, elevated levels of inflammatory markers have been reported in CKD even in its early stages [18,19], underlining that inflammation plays a significant role in predicting progression of kidney dysfunction and in the pathogenesis of AF [20,21]. Imaging techniques such as echocardiography could be helpful to evaluate morphological and functional cardiac indicators of thromboembolic risk in patients with CKD [22][23][24], especially in cases of treatment with vitamin K antagonists out of therapeutic range or with NOACs in the presence of poor compliance [25,26].…”
Section: Discussionmentioning
confidence: 99%